Factors Affecting Impact Investment among Generation Z: The Moderating Role of Behavioral Biases - Chowdhary, Priyanka; Pandey, Manoj; Singh, Prakash; Sharma, Praveen Kumar; Shukla, Aparna (International Review of Management and Marketing, 2025)
This study explores the determinants that affect impact investment behavior, with a particular emphasis on the moderating influence of behavioral biases. The inquiry examines principal factors influencing impact investment, encompassing environmental concern, environmental awareness, social norms, perceived behavioral control, and attitudes. Additionally, the study investigates how behavioral biases affect the relationship between these factors and impact investment decisions. Employing SmartPLS, structural equation modeling analysis demonstrates that environmental concern, social norms, and perceived behavioral control exert a significant influence on investment behaviors. However, behavioral biases do not appear to moderate the association between attitudes and investment behavior.